A Review - Future Aspect of Natural Fiber Reinforced Composite. Issue 2 (May 2016) - Rohit, Kiran; Dixit, Savita
Natural fiber-reinforced polymer composite materials are rapidly growing both in terms of their industrial applications and fundamental research as they are renewable, low, completely or partially recyclable and biodegradable. In order to produce cost effective polymer reinforced composites and to reduce the destruction of ecosystem, researchers have come up with new manufacturing trends for composite using natural fibers which are partially biodegradable, for which plants such as flax, cotton, hemp, jute, sisal, kenaf, pineapple, banana, wood etc., used from time immemorial as a rich source of lignocellulosic fibers are more often applied as the reinforcement of composites. Their abundant availability, low cost and density as well as satisfactory mechanical properties make them an attractive ecological alternative for the manufacturing of composites. The natural fiber based composites is more environmentally friendly and has variety of applications in the field of transportation (automobiles, railway coaches, aerospace) building and construction industries (ceiling paneling, partition boards), packaging, consumer products, etc. The demand for wood products is continuously rising in spite of rapid depletion of forest around the world. Research in the area of green technology is being done to provide wood substitutes which make use of wood materials mixed with a polymer to provide a cost effective, improved performance and termite resistant material. The use of wood flour filled polymer composites has been considerably studied from the scientific and commercial point of view over the last decades. Wood flour is an attractive filler for polymer due to their reduced environmental impact and globally pleasant aesthetical properties. They are also low cost and low density material and high specific, biodegradable and non abrasive during processing. This article is a critical review of the most recent development natural fiber composite and the summary of the result presented in literature.